Endoscopic dacryocystorhinostomy - Rasan, M.I.; Shailendra, S.; Prepageran, Narayanan; Gopala, K.; Sathananthar, K.S. (Malaysian Medical Association, 2008)
A review of 45 patients who underwent endoscopic dacryocystorhinostomy (EDCR) from 1998 to 2005 was done. Only patients who had complete notes and had Jones tube removed at least three months before the study were included. Our experience with EDCR concludes it to be an easy, efficient treatment for nasolacrimal duct obstruction with minimal complications.